THE ESSENCE, FUNCTIONS, AND ROLE OF THE HEALTHCARE SYSTEM IN SOCIETAL DEVELOPMENT - Kasimova D.A,; Rustamova D.A,; Davlatova Y.Ch, (TADQIQOTLAR, 2026)
Annotation: This article examines the essence of the healthcare system, its main functions, and its role in the socio-economic development of society. Healthcare is considered  as  a  key  component  of  social  infrastructure  that  directly  influences population health, labor productivity, and overall quality of life. The study analyzes the organizational, economic, and social aspects of healthcare systems, highlighting their  importance  in  ensuring  public  health  protection  and  sustainable  development. Special  attention  is  paid  to  the  interrelation  between  healthcare  effectiveness  and national development, as well as the need for continuous reforms and modernization of  healthcare  services.  The  findings  emphasize  that  a  well-functioning  healthcare system is a fundamental factor in strengthening human capital and achieving long-term societal progress.